Fetal malnutrition and associated factors among term newborn babies in Jimma Zone public hospitals, South West Ethiopia - Aynadis Awoke; Aynalem Yetwale; Tsegaw Biyazin; Tegegn Wolde; Makeda Sinaga (PLoS ONE, 2025)
Background Fetal malnutrition is a major public health burden affecting developing nations, potentially leading to cerebral and neurologic disabilities in later life. Despite its prevalence, little is known about its associated factors in the study area. Thus, this study aimed to assess prevalence and associated factors of fetal malnutrition among term newborn babies in Jimma Zone Public Hospitals. Method A cross-sectional study was carried out among 449-term newborns using systematic sampling techniques in Jimma Zone Public Hospitals from April 1, 2024, to July 30, 2024. Maternal data were collected using an interviewer-administered questionnaire and newborn data were collected using clinical assessment of fetal nutrition (CAN score) scoring system and entered into Epi-data version 4.6 and exported to SPSS version 26 for analysis. Bivariate logistic regression was performed and variables with a p-value ≤0.25 were entered into multivariable logistic regression analysis. P-value less than 0.05 were considered statistically significant and data were presented using text, figures, and tables. Result A total of 449 newborns with their mothers were involved in the study with the response rate of 100%. The prevalence of fetal malnutrition was 91/449 (20.3%) (95% CI, 16.5–24). Among delivered newborns 229/449 (51%) were females and the remaining are males. Maternal age less than nineteen was 60/449 (13.4%) (AOR = 2.930, 95% CI (2.518–13.967)), maternal MUAC ≤23 were 181/449 (40.3%) (AOR = 4.094, 95% CI (2.155–7.77)), infection during pregnancy 97/449 (21.6%) (AOR = 2.729, 95% CI (1.286–5.792)), malaria 99/449 (22%) (AOR = 2.125, 95% CI (1.002–4.510)), not taking Iron and Folic Acid 300/449 (66.8%) (AOR = 2.897, 95% CI (1.330–6.309)), complication during current pregnancy 116/449 (25.8%) (AOR = 4.629, 95% CI (2.444–8.767)), anemia 301/449 (67%) (AOR = 3.669, 95% CI (1.968–6.840)), low birth weight 77/449 (17.1%) (AOR = 5.363, 95% CI (2.760–10.420)), low placental weight 204/449 (45.4%) (AOR = 4.984, 95% CI (2.530–9.816)), antenatal depression 153/449 (34%) (AOR = 7.184, 95% CI (3.733–13.827)), and intimate partner violence 153/449 (34%) (AOR = 5.613, 95% CI (3.011–10.328)), were significantly associated with fetal malnutrition. Conclusion The prevalence of fetal malnutrition in this study indicates one in five delivered newborn. Newborns with low birth weight, low placental weight, and mothers having anemia, intimate partner violence (IPV), antenatal depression, teenage pregnancy, malaria, infection, and complications during pregnancy were a strong association with fetal malnutrition. Therefore, this study recommends that all concerned bodies, should prioritize efforts to reduce intimate partner violence, prevent infections during pregnancy, enhance maternal nutrition counseling, and address the issue of teenage pregnancy.